Interleukin-1 receptor-dependent and -independent caspase-1 activity in retinal cells mediated by receptor interacting protein 2 - Coughlin, Brandon A.; Christian, Barbara; Trombley, Brett; Mohr, Susanne (Frontiers in Cell and Developmental Biology, 2024)
Inflammation and cell death play an important role in the pathogenesis of diabetic retinopathy. Previously we observed sustained activation of pro-inflammatory caspase-1 in retinas of diabetic animals and patients. In this study, we aimed to look at mechanisms underlying chronic caspase-1 activation in vitro and in vivo. Our in vivo results demonstrate that caspase-1 activation progresses from an IL-1 receptor (IL-1R1) independent mechanism at 10 weeks of diabetes to an IL-1R1 dependent mechanism at 20 weeks indicating that feedback through IL-1R1 is crucial for sustained caspase-1 activity in retinas of STZ (streptozotocin) mice. A similar hyperglycemia-mediated caspase-1/IL-1b/IL-1R1 feedback signaling was detected in vitro in human Müller cells which was prevented by treatment with an IL-1 receptor antagonist (IL-1ra). Our data also indicate that hyperglycemia induces caspase-1 activation initially but IL-1b sustains caspase-1 activation via caspase-1/IL-1b/IL-1R1 feedback and we identified Receptor Interacting Protein-2 (RIP2) as mediator of both hyperglycemiaand IL-1b-induced caspase-1 activation. Activation of caspase-1/IL-1b/IL-1R1 feedback signaling caused Müller cell death which was prevented by RIP2 knockdown. We conclude that any intervention in caspase-1/IL-1b/IL-1R1 feedback signaling presents novel therapeutic options for the treatment of diabetic retinopathy.